0

# What is 3t minus 7 equals 5 then 6t equals?

Updated: 9/27/2023

Wiki User

6y ago

Be notified when an answer is posted

Earn +20 pts
Q: What is 3t minus 7 equals 5 then 6t equals?
Submit
Still have questions?
Related questions

### How do you factor 6t squared 7t-5?

If that's + 7t, the answer is (3t + 5)(2t - 1) If that's - 7t, the answer is (3t - 5)(2t + 1)

### What is s and t when 2s add 3t is 28 and 5s add 6t is 61?

That's a simple example of system of equations. There are quite a number of methods for solving those, but the easiest here would be to calculate one variable from first equation and substitute it into second. 2s + 3t = 28 5s + 6t = 61 Let's calculate s from the first equation: 2s + 3t = 28, 2s = 28 - 3t s = 14 - 3t/2 Substitute s into second equation 5s + 6t = 61, 5(14 - 3t/2) + 6t = 61, 70 - 15t/2 + 6t = 61, 70 - 3t/2 = 61, 3t/2 = 9, t = 6. We can then substitute t back into first equation: 2s + 3t = 28, 2s + 3 * 6 = 28, 2s = 10, s = 5. So the final answer is: s = 5 t = 6

### How do you factor 6t squared-7t-5 divided by 3t-5?

It's a simple problem in long division and the answer is 2t + 1

### What does t equal in the eqation 5-3t equals 0.77?

5-3t = 0.77 -3t = 0.77-5 -3t = -4.23 t = 1.41

### What is the answer for 8t plus 5 equals 6t plus 1?

8t + 5 = 6t + 1,subtract 6t an 5 from each side,2t = -4t = -2Checking, 8t + 5 = -16 + 5 = -11 and 6t +1 = -12 + 1 = -11

### Solve for t in the equation 3t plus 7 equals 2t-5?

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

17

### If a equals 3 and bequals minus 5 then a minus b equals?

If a equals 3 and b equals minus 5 then a minus b equals what

t=-2

-12t+4

15t+25 = 5(3t+5)

t = -11/10